MANAJEMEN PEMERINTAHAN DAERAH DALAM PENGELOLAAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) DI KOTA PEKANBARU TAHUN 2018-2019 - Siti Rahmah; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Simple Flats Rental (Rusunawa) is a program that aims to ensure the fulfillment of the need for a decent and affordable place to live, especially for low-income people (MBR) in a comfortable, healthy and safe environment. The problem in this study is the lack of optimal management of Simple Rent Flats (Rusunawa) Pekanbaru City.            This study aims to find out how Government Management in The Management of Simple RentEd Flats (Rusunawa) in Pekanbaru City, and to know the factors that affect Government Management In The Management of Simple Rental Flats (Rusunawa) in Pekanbaru City both internal and external factors. The research approach used is qualitative approach and this type of research is descriptive. The location of this research was conducted at the Public Housing Office and Pekanbaru City Residential Area, the collection technique was conducted with interviews and documentation.            The result of this study is that first, Local Government Management in The Management of Simple Rented Flats (Rusunawa) In Pekanbaru City in 2018-2018 has been done with less than optimal, where in running management related to the management of rusunawa has not shown the stage of success. Second, the factors that affect the management of Simple Rent Flats (Rusunawa) in Pekanbaru City are the enforcement of sanctions against residents who do not pay rent, lack of maintenance rusunawa, inadequate transportation facilities, and low public interest to inhabit rusunawa.   Keywords: Government Management, Management, Simple Flats Rental (RUSUNAWA)